Harnessing the immune system in glioblastoma. Issue 10 (13th November 2018) - Brown, Nicholas; Carter, Thomas; Ottaviani, Diego; Mulholland, Paul
Abstract Glioblastoma is the most common primary malignant brain tumour. Survival is poor and improved treatment options are urgently needed. Although immunotherapies have emerged as effective treatments for a number of cancers, translation of these through to brain tumours is a distinct challenge, particularly due to the blood–brain barrier and the unique immune tumour microenvironment afforded by CNS-specific cells. This review discusses the immune system within the CNS, mechanisms of immune escape employed by glioblastoma, and the immunological effects of conventional glioblastoma treatments. Novel therapies for glioblastoma that harness the immune system and their current clinical progress are outlined, including cancer vaccines, T-cell therapies and immune checkpoint modulators.